Moving Target Signals in High Resolution Wide Swath SAR - Gabele, Martina; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
In this paper the impact of two high resolution wide swath synthetic aperture radar imaging techniques, extraction of signals from azimuth subsampled spectra and subpulse azimuth beamsteering on transmit, on ground moving target signals is analyzed. A modelling of the interfering signals in range-Doppler domain is introduced, that is suitable for studying the performance of low PRF sampled GMTI and subpulse beamsteering in azimuth and elevation on transmit and receive for HRWS-SAR imaging and GMTI. The combination of the two techniques yields an operation mode for high resolution wide swath synthetic aperture radar imaging and long observation time wide swath ground moving target indication. The mode is analyzed in terms of signal to interference plus noise ratio and coverage for ground moving target indication.
DLR Import::2019-04-03